Pengaruh Biaya Produksi Terhadap Laba Bersih Perusahaan Dengan Volume Penjualan Sebagai Variabel Moderating - Baihaqi Ammy (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This research uses associative and quantitative types. This study uses secondary data collection techniques in the form of corporate financial reports for the period 2016-2019. The population in this study were 21 companies and the samples in this study were 14 companies. The data analysis technique used descriptive statistical testing, multiple linear regression, classical assumption test, hypothesis test, moderation regression analysis, and determination coefficient test. The results of this study indicate that production costs have a positive and significant effect on company net income and sales volume shows a negative and significant effect on company net income, besides that it is also known that sales volume does not moderate the effect of production costs on company net income. Keywords: Current ratio, Debt to equity ratio, Return on equity, Price to book value.